Niche dynamics along two centuries of multiple crayfish invasions - Viana, Duarte S; Oficialdegui, Francisco J; Soriano, María Del Carmen; Hermoso, Virgilio; Clavero, Miguel (The Journal of animal ecology, 2023)
The realised ecological niches of species may change in response to dynamic abiotic and biotic environments, particularly under fast global change. To fully understand the dynamics of niche features and their drivers, it is essential to have a long-term view of species distributions and the factors that may have influenced them. Here, we analysed the distribution and niche dynamics of the Italian crayfish (Austropotamobius fulcisianus) in the Iberian Peninsula over the past 200 years. The Italian crayfish was introduced to Spain in the 16th century, and spread due to multiple stocking events until the 1970s, when two North American crayfish (red swamp crayfish Procambarus clarkii, and signal crayfish Pacifastacus leniusculus) were introduced. Both North American species are carriers of a pathogen (Aphanomyces astaci, the causal agent of crayfish plague) lethal to the Italian crayfish. We hypothesised that the realised niche of the Italian crayfish, both in breadth and in position, has changed over time following changes in its range. The distribution of the Italian crayfish expanded from the mid-19th century until the mid-20th century, in association with an enlargement of its realised niched, mostly towards less abrupt and more coastal-influenced areas. After the introduction of the North American crayfishes, the collapse of the Italian crayfish involved a niche shift towards rough terrains in mountain areas. North American crayfish have eventually occupied most of the Italian crayfish's niche space, with the few no-coexistence areas being relegated to the most abrupt and high-elevation territories. Our historical approach allowed us to document and understand the highly dynamic distribution and niche of the Italian crayfish in the presence of invader counterparts, and to explore the environmental conditions under which their coexistence is minimised.
Keywords: Astacoidea; Animals; species distribution models; Španělsko; ekosystém; niche shifts; Ecosystem; Europe; biological invasions; zvířata; Evropa; Spain; severní raci; historical ecology; freshwater crayfish; Aphanomyces